Revamping Career Management and Development Professional Identity in Organizational: Context Review - Helmi, Ahmad; Nurhaji, Soffan (Pusat Pengembangan Sumber Daya Manusia Aparatur, 2023)
Disruption flows cover aspects of human social life, starting from oneself and the environment. Given the inherent interplay of digitalization, automation, and robotization, the environment requires the industry to quickly anticipate new consumer values, trends, and needs and adjust production accordingly, requiring adaptive competence and content-based models. This review (1) briefly describes the competency-based development model; (2) presents difficulties when defining and describing the differences between competencies, skills, and abilities; (3) presents the challenge of competency measurement; (4) presents the latest findings from competency content models in organizational and individual contexts; and (5) Challenges that this model might face in the future. This systematic approach with the PRISMA Flow Diagram method enhances the credibility of the review but also contributes to a deeper understanding of the dynamics between career management, professional identity, and organizational contexts. After running the searches in the databases, selecting and adding the records identified from other sources, combine all the descriptions returned from the searches into one citation management program, Mendeley. The literature review was conducted to summarize relevant published research studies and to define future research directions. The results suggest that further resource research should focus on generalizing findings by looking at different groups of workers and organizations, broadening the range of resources used in the analysis, using different definitions of crucial resources, and developing alternative models to assess their impact on performance. Such research will make it possible to evaluate employee resilience in terms of competency requirements to assess employee resilience better and identify the most critical gaps and opportunities for the formal education system and as part of on-the-job training. ABSTRAKArus disrupsi melingkup aspek kehidupan sosial manusia mulai dari diri sendiri dan lingkungan. Lingkup lingkungan menuimbulkan interaksi digitalisasi, otomatisasi, dan robotisasi yang melekat, industri perlu dengan cepat mengantisipasi nilai, tren, dan kebutuhan konsumen baru serta menyesuaikan produksinya, sehingga membutuhkan adaptasi kompetensi dan model berbasis kompetensi yang adaptif. ulasan ini: (1) menguraikan secara singkat pengembangan model berbasis kompetensi; (2) menghadirkan kesulitan saat mendefinisikan dan menggambarkan perbedaan antara kompetensi, keterampilan, dan kemampuan; (3) menyajikan tantangan utama pengukuran kompetensi; (4) menyajikan temuan terbaru dari model berbasis kompetensi dalam konteks organisasi dan individu; dan (5) menyoroti tantangan yang mungkin dihadapi model ini di masa depan. Pendekatan sistematis dengan metode Diagram Alir PRISMA ini, meningkatkan kredibilitas tinjauan namun juga berkontribusi pada pemahaman yang lebih mendalam tentang dinamika antara manajemen karir, identitas profesional, dan konteks organisasi. Setelah menjalankan pencarian di database, memilih, dan menambahkan catatan, diidentifikasi dari sumber lain, menggabungkan semua catatan yang dikembalikan dari pencarian ke dalam satu program manajemen kutipan Mendeley. Tinjauan literatur dilakukan pada penelitian berbasis kompetensi yang fokus pada generalisasi temuan dengan melihat berbagai kelompok pekerja dan organisasi, memperluas rangkaian kompetensi yang digunakan dalam analisis, menggunakan definisi kompetensi kunci yang berbeda, dan mengembangkan model alternatif untuk menilai dampaknya terhadap pertunjukan. Secara konteks akan memungkinkan untuk menilai kesiapan SDM dengan lebih baik dalam hal persyaratan kompetensi, serta mengidentifikasi celah dan peluang paling kritis untuk sistem pendidikan formal dan sebagai bagian dari pelatihan di tempat kerja.